The Effectiveness of Islamic Counseling as a Da’wah Approach to Increase the Religious Awareness of Ex-prostitutes - Silvianetri Silvianetri; Irman Irman; Khairunnas Rajab; Zulamri Zulamri; Zubaidah Zubaidah; Zulfikar Zulfikar (Jurnal Dakwah Risalah, 2022)
One of the problems experienced by ex-prostitutes was the low awareness of religion. This impacted their daily behavior in which they could be easily influenced to return to their old profession as prostitutes. A treatment that was considered appropriate to increase the religious awareness of ex-prostitutes is Islamic counseling as a da'wah approach. This study aimed to examine the effectiveness of Islamic counseling as a da'wah approach to improve the religious awareness of ex-prostitutes. This study used an experimental approach with a single-subject multiple baseline design. The respondents were three ex-prostitutes who stayed in a social rehabilitation institution. The research instrument used was a religious awareness scale. Data were analyzed using trend analysis. The study found that Islamic counseling as a da'wah approach effectively increased the religious awareness of ex-prostitutes so that ex-prostitutes can return to the community properly.